Distribution of Tree Canopy-Level Vegetation in Mandiangin Hill, Banjar Regency - Susilawati, Susilawati; Pujawati, Eny Dwi; Agustina, Arfa; Busthami, Yazid; Novialita, Dwi Revina (Pattimura University Ambon Maluku Indonesia, 2022)
The high diversity of tree species at various height levels indicates that there may still be many unidentified tree species, making it unclear how the distribution and abundance of the tree community's structure are. The ULM Special Purpose Forest Area (KHDTK ULM) covers an area of 1,617 hectares. The KHDTK ULM includes several regions such as Bukit Besar, Bukit Mandiangin, Bukit Pamaton, and Bukit Pandamaran, each with different elevations. Research on the structure of the tree community at Bukit Mandiangin is necessary for the preservation of germplasm in the KHDTK ULM. The objectives of this research are (1) to assess the presence of tree species at different elevations, (2) to analyze the distribution and abundance of tree species at different elevations, and (3) to analyze the diversity, evenness, and similarity of tree species communities at different elevations